Compliance considerations with hormone replacement therapy - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 1998)
Objective: The purpose of this study was to determine women's own reasons for postmenopausal hormone replacement therapy (HRT) utilization and discontinuation in a Turkish population and to investigate the variables that have influenced the compliance to treatment. Design: The study was comprised of 613 postmenopausal women who presented to the Menopause Unit in the Marmara University Hospital. Results: A total of 437 women (71.2%) reported that they continued using postmenopausal HRT and 176 women (28.7%) discontinued treatment with an average 4.5 months duration of use (range 1-60 months). Hot flashes was the most common reason for initiating therapy (258 women, 42.0%). Prevention of osteoporosis was mentioned by 149 (24.3%) women as a reason to begin HRT. Bleeding episodes (44.8%) was the most common factor in the patient's decision to discontinue HRT. Continuation of HRT was significantly more common among women who started HRT either because of physician recommendation or osteoporosis concern (p < 0.05). Additionally, a greater percentage of surgically menopausal women began and continued HRT(p < 0.0001) than naturally menopausal women. The educational status of the patients was directly related to incidence of beginning HRT but was not related to the discontinuation of HRT. Conclusions: Education of menopausal women about the long-term benefits of HRT is critical in improving compliance. (C) 1998, The North American Menopause Society.
Keywords: hormone replacement therapy; compliance; menopause; WOMENS KNOWLEDGE; ATTITUDES; INFORMATION; MENOPAUSE; DISEASE